TUBA4A downregulation as observed in ALS post-mortem motor cortex causes ALS-related abnormalities in zebrafish - Van Schoor, Evelien; Strubbe, Dufie; Braems, Elke; Weishaupt, Jochen; Ludolph, Albert C.; Van Damme, Philip; Thal, Dietmar Rudolf; Bercier, Valérie; Van Den Bosch, Ludo (Frontiers in Cellular Neuroscience, 2024)
Disease-associated variants of TUBA4A (alpha-tubulin 4A) have recently been identified in familial ALS. Interestingly, a downregulation of TUBA4A protein expression was observed in familial as well as sporadic ALS brain tissue. To investigate whether a decreased TUBA4A expression could be a driving factor in ALS pathogenesis, we assessed whether TUBA4A knockdown in zebrafish could recapitulate an ALS-like phenotype. For this, we injected an antisense oligonucleotide morpholino in zebrafish embryos targeting the zebrafish TUBA4A orthologue. An antibody against synaptic vesicle 2 was used to visualize motor axons in the spinal cord, allowing the analysis of embryonic ventral root projections. Motor behavior was assessed using the touch-evoked escape response. In post-mortem ALS motor cortex, we observed reduced TUBA4A levels. The knockdown of the zebrafish TUBA4A orthologue induced a motor axonopathy and a significantly disturbed motor behavior. Both phenotypes were dose-dependent and could be rescued by the addition of human wild-type TUBA4A mRNA. Thus, TUBA4A downregulation as observed in ALS post-mortem motor cortex could be modeled in zebrafish and induced a motor axonopathy and motor behavior defects reflecting a motor neuron disease phenotype, as previously described in embryonic zebrafish models of ALS. The rescue with human wild-type TUBA4A mRNA suggests functional conservation and strengthens the causal relation between TUBA4A protein levels and phenotype severity. Furthermore, the loss of TUBA4A induces significant changes in post-translational modifications of tubulin, such as acetylation, detyrosination and polyglutamylation. Our data unveil an important role for TUBA4A in ALS pathogenesis, and extend the relevance of TUBA4A to the majority of ALS patients, in addition to cases bearing TUBA4A mutations.